CD28 Family and Chronic Rejection: "To Belatacept...and Beyond!". (7th June 2012) - Silva, Marcos V.; Machado, Juliana R.; Rocha, Laura P.; Castellano, Lúcio R.; Reis, Marlene A.; Corrêa, Rosana R. M.
Abstract : Kidneys are one of the most frequently transplanted human organs. Immunosuppressive agents may prevent or reverse most acute rejection episodes; however, the graft may still succumb to chronic rejection. The immunological response involved in the chronic rejection process depends on both innate and adaptive immune response. T lymphocytes have a pivotal role in chronic rejection in adaptive immune response. Meanwhile, we aim to present a general overview on the state-of-the-art knowledge of the strategies used for manipulating the lymphocyte activation mechanisms involved in allografts, with emphasis on T-lymphocyte costimulatory and coinhibitory molecules of the B7-CD28 superfamily. A deeper understanding of the structure and function of these molecules improves both the knowledge of the immune system itself and their potential action as rejection inducers or tolerance promoters. In this context, the central role played by CD28 family, especially the relationship between CD28 and CTLA-4, becomes an interesting target for the development of immune-based therapies aiming to increase the survival rate of allografts and to decrease autoimmune phenomena. Good results obtained by the recent development of abatacept and belatacept with potential clinical use aroused better expectations concerning the outcome of transplanted patients.